2002
DOI: 10.1002/cncr.10665
|View full text |Cite
|
Sign up to set email alerts
|

New WHO histologic classification predicts prognosis of thymic epithelial tumors

Abstract: BACKGROUNDIn 1999, a World Health Organization (WHO) committee published histologic criteria for distinct thymoma entities (labeled as Type A, AB, B1, B2, B3 thymomas) and for the heterogeneous group of thymic carcinomas, collectively called Type C thymomas. Whether WHO‐defined histologic thymoma subtypes are of independent prognostic relevance has yet to be proved.METHODSTwo hundred thymomas from the Shanghai Chest Hospital with a mean follow‐up time of 15 years (range, 1–246 months) were studied for the rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

26
279
5
18

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 355 publications
(328 citation statements)
references
References 34 publications
26
279
5
18
Order By: Relevance
“…10,45,46 The proportion of patients with recurrence was higher in stages III and IV compared with patients in stages I and II. 38,45 As most of the recurrent cases in this study were stage I or II at diagnosis, it was not useful in predicting the behavior of these tumors. In an analysis of 1320 thymic tumors, Kondo and Monden 47 found total resection as the most significant predictive factor.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…10,45,46 The proportion of patients with recurrence was higher in stages III and IV compared with patients in stages I and II. 38,45 As most of the recurrent cases in this study were stage I or II at diagnosis, it was not useful in predicting the behavior of these tumors. In an analysis of 1320 thymic tumors, Kondo and Monden 47 found total resection as the most significant predictive factor.…”
Section: Discussionmentioning
confidence: 79%
“…With the continued perception of benign behavior, it is probable that some patients will not receive due consideration for adjuvant therapy. 21,38,39 Regarding type AB thymoma, the 2004 WHO update states: 'type AB thymomas are generally regarded as clinically benign tumors.' 6 Paradoxically, it also states that up to 25% of AB thymomas can be invasive at diagnosis (stage II or greater).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[44][45][46][47][48][49] Some reports have shown that patients with type B3 thymoma have a worse prognosis than those with type B2 thymoma, 44,45 whereas others have reported no significant difference in survival between these 2 groups. [46][47][48][49] The results of the current study indicated no difference in the 10-year OS rates between patients with type B1 þ B2 (89.5%) and type B3 (75.0%) thymomas (P ¼ .30), whereas significant differences (P < .001) were noted between patients with type B1 þ B2 (86% and 85%, respectively) and type B3 (38%) thymomas in a previous report from our institution. 44 A possible reason is the difference in the period of analysis; the analysis of the current study was conducted between 1999 and 2009 for thymoma, whereas that of the previous report was performed between 1962 and 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated that the WHO histologic classification reflects the oncologic behavior of thymoma. 40,41 Type A and AB thymomas are benign, and Type B1 and B2 thymomas represent the borderline between benign and malignant thymoma. Conversely, Type B3 thymomas have malignant behavior, and Type C thymomas are more aggressive tumor and must be considered cancerous.…”
Section: Discussionmentioning
confidence: 99%